2016
DOI: 10.1104/pp.16.00525
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Polymorphisms at the REDUCED DORMANCY5 Pseudophosphatase Underlie Natural Variation in Arabidopsis Dormancy

Abstract: Seed dormancy controls the timing of germination, which regulates the adaptation of plants to their environment and influences agricultural production. The time of germination is under strong natural selection and shows variation within species due to local adaptation. The identification of genes underlying dormancy quantitative trait loci is a major scientific challenge, which is relevant for agricultural and ecological goals. In this study, we describe the identification of the DELAY OF GERMINATION18 (DOG18)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 45 publications
5
57
0
2
Order By: Relevance
“…Peptides were analyzed with a QExactive Plus mass spectrometer (Thermo Fisher Scientific Inc., MA, USA) with a Top15 method with exactly the same parameters as described in ref. .…”
Section: Methodsmentioning
confidence: 99%
“…Peptides were analyzed with a QExactive Plus mass spectrometer (Thermo Fisher Scientific Inc., MA, USA) with a Top15 method with exactly the same parameters as described in ref. .…”
Section: Methodsmentioning
confidence: 99%
“…RDO5 is a member of the PP2C family of protein phosphatases that does not show phosphatase activity 1315 . The molecular function of DOG1 has not been solved and its protein lacks domains with a known function.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, field experiments using a diallel cross between accessions from Sweden and Italy identified a major QTL associated with total fitness that spanned the DOG1 region, and also demonstrated that genetic differences in seedling establishment—and most particularly in seed dormancy—are one of the main components of local adaptation (Postma and Ågren, 2016; Postma et al, 2016; Huang et al, 2010a). Finally, extensive natural variation for seed dormancy is not unique to the DOG1 locus and many other QTLs have been mapped in various populations (Alonso-Blanco et al, 2003; Bentsink et al, 2006, 2010; Amiguet-Vercher et al, 2015; Xiang et al, 2016). The recent cloning of the DELAY OF GERMINATION18 ( DOG18 )/ IBO QTLs in two independent diallel crosses revealed the existence of numerous loss-of-function alleles—mainly caused by nonsense mutations and structural variants—at the REDUCED DORMANCY5 ( RDO5 ) locus in wild A. thaliana populations (Xiang et al, 2016; Amiguet-Vercher et al, 2015; Xiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, extensive natural variation for seed dormancy is not unique to the DOG1 locus and many other QTLs have been mapped in various populations (Alonso-Blanco et al, 2003; Bentsink et al, 2006, 2010; Amiguet-Vercher et al, 2015; Xiang et al, 2016). The recent cloning of the DELAY OF GERMINATION18 ( DOG18 )/ IBO QTLs in two independent diallel crosses revealed the existence of numerous loss-of-function alleles—mainly caused by nonsense mutations and structural variants—at the REDUCED DORMANCY5 ( RDO5 ) locus in wild A. thaliana populations (Xiang et al, 2016; Amiguet-Vercher et al, 2015; Xiang et al, 2014). …”
Section: Introductionmentioning
confidence: 99%